Pengaruh Metode Inquiry Terhadap Kemampuan Komunikasi Matematis Siswa SMP Negeri 6 Kota Tangerang Selatan - Izzah, Nailie (Jurnal Gemaedu, 2018)
The purpose of this study is to find out how much influence inquiry method of students' mathematical communication skills in class VIII SMP Negeri 6 Kota Tangerang. The research method used is quasi-experiment. The population in this study is all students of SMP Negeri 6 Kota Tangerang Selatan, while the sample was taken as many as 76 students consisting of 38 students experimental group and 38 students control group. The sampling technique using simple random sampling (simple random sampling). The instrument for data collection in this research is essay test consist of 15 problems. The data analysis technique used is t-test, and based on t-test calculation shows t-count = 4.08 and t-table = 1,992 at significance level of 5% or (α = 0,05) which means thitung> t-table (4,08> 1,992 ), then H0 is rejected and H1 is accepted. so it can be concluded that there are differences in the results of mathematical communication skills between students taught by inquiry method with students taught by the problem-solving method. Based on it can be said that the results of mathematical communication skills in students who are taught by inquiry method is higher than students taught by the problem-solving method.